PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN TOILET LEARNING TERHADAP PENGETAHUAN IBU PADA ANAK USIA TODDLER DI PAUD MAWAR RW 06 KELURAHAN TLOGOMAS MALANG - Atti yudiernawati; Nur Astariani (Universitas Tribhuwana Tunggadewi, 2014)
Education of the toilet learning is a learning process and one of the form of treatment intervention of the toilet learning through training programs on the toilet learning to enhance knowledge mother in toilet learning. This study aims to know the effect (the influence) of the giving of health education to the knowledge mother in toilet learning on toddler age children in PAUD Mawar RW 06 Village of Tlogomas Malang. Research design used pre-experimental that is one-group pre-post test design. Population is all the mothers who have the toddler age children in PAUD Mawar RW 06 Village of Tlogomas Malang as many as 35 people. The sample in this study as many as 14 people. Sampling with accidental sampling. Data were analyzed by using paired T-test with a significance level (0,05). The knowledge of mother in toilet learning before being given health education in the enough category as many as 10 people (71.4%) and less category is 4 people (28.6%), while after the education given in the good category as many as 12 people (85.7% ) and enough category is 2 people (14.3%). The result of analysis showed p value = 0.00 means p value < (0,05). It means that there is the effect of giving of the toilet learning health education on knowledge mother on toddler age children in PAUD Mawar RW 06 Village of Tlogomas Malang. Suggestions that can be recommended for further researcher, if they want to do research/study about mother knowledge in toilet learning should the age of children under 18 months in order to get maximum result.